2010
DOI: 10.1162/jocn.2009.21351
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Spatial Working Memory to Visuomotor Learning

Abstract: Previous studies of motor learning have described the importance of cognitive processes during the early stages of learning; however, the precise nature of these processes and their neural correlates remains unclear. The present study investigated whether spatial working memory (SWM) contributes to visuomotor adaptation depending on the stage of learning. We tested the hypothesis that SWM would contribute early in the adaptation process by measuring (i) the correlation between SWM tasks and the rate of adaptat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
325
8
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(371 citation statements)
references
References 156 publications
(141 reference statements)
33
325
8
5
Order By: Relevance
“…Similarly, low-level neural circuits in the primary motor cortex and the cerebellum have been assumed to constrain the generalization of motor learning across directions (Thoroughman and Shadmehr, 2000;Donchin et al, 2003;Paz et al, 2003;Shadmehr, 2004). Based on our findings, we suggest that motor generalization should also engage an extensive range of brain regions, including the striatum and the prefrontal and parietal cortices, which are closely related to reinforcement learning and cognitive learning (Tanaka et al, 2009;Anguera et al, 2010;Wächter et al, 2010).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Similarly, low-level neural circuits in the primary motor cortex and the cerebellum have been assumed to constrain the generalization of motor learning across directions (Thoroughman and Shadmehr, 2000;Donchin et al, 2003;Paz et al, 2003;Shadmehr, 2004). Based on our findings, we suggest that motor generalization should also engage an extensive range of brain regions, including the striatum and the prefrontal and parietal cortices, which are closely related to reinforcement learning and cognitive learning (Tanaka et al, 2009;Anguera et al, 2010;Wächter et al, 2010).…”
Section: Discussionsupporting
confidence: 52%
“…Reinforcement learning, a form of model-free learning, is an operant association between the adapted movement and the successful error reduction (Diedrichsen et al, 2010;Huang et al, 2011;Verstynen and Sabes, 2011;Shmuelof et al, 2012). From a different perspective, motor adaptation is also divided into an explicit component, which is closely related to cognitive strategies, and an implicit component (Anguera et al, 2010;Fernandez-Ruiz et al, 2011;Taylor et al, 2014;McDougle et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…During the process of learning motor skills, tracing of visuospatial constellations and limbs trajectories are likely essential. Indeed, a study on visuomotor adaptation in adults without any disorders indicates that people recall the visuomotor map, update this map using spatial working memory resources, and then use this updated map to plan subsequent movements (Anguera, Reuter-Lorenz, Willingham, & Seidler, 2010). In other words, if visual memory is poor, it might be difficult to execute such motor planning, inhibiting effective control of the limbs.…”
Section: Discussionmentioning
confidence: 99%
“…Given the exposition so far, perhaps it is not surprising that people with higher WM capacity also perform better on long-term episodic memory tests (Anguera et al, 2012;Anguera, Reuter-Lorenz, Willingham, & Seidler, 2010;Marevic, Arnold, & Rummel, 2017;Unsworth, Brewer, & Spillers, 2009;Unsworth & Spillers, 2010). Multinomial modeling has revealed that WM capacity correlates with encoding success, rather than with retrieval probability (Marevich et al, 2017).…”
Section: Better Ltm For People With More Wm Capacitymentioning
confidence: 99%